2018
DOI: 10.2214/ajr.17.18496
|View full text |Cite
|
Sign up to set email alerts
|

Single-Contrast CT for Detecting Bowel Injuries in Penetrating Abdominopelvic Trauma

Abstract: Single-contrast CT can show bowel injuries in patients with penetrating abdominopelvic trauma with accuracy comparable with that reported for triple-contrast CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 39 publications
0
39
1
Order By: Relevance
“…Certain authors have reported benefits of using a triple contrast protocol (oral, rectal, and i.v.) (6,9,11,12), while others have reported similar results for sensitivity and specificity of CT with intravenous contrast material only (8).…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Certain authors have reported benefits of using a triple contrast protocol (oral, rectal, and i.v.) (6,9,11,12), while others have reported similar results for sensitivity and specificity of CT with intravenous contrast material only (8).…”
Section: Introductionmentioning
confidence: 60%
“…In our material, SWs were the most common cause of penetrating abdominal trauma and young men were most often involved, which is in accordance with studies from other European countries (1517). However, in studies based on patient data from the United States, GSWs tend to be more prevalent (5,8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In stable and semistable patients, CT is the gold standard of evaluation. Although there are numerous CT scanning protocols proposed in the literature, 25 -34 by consensus the authors of this article advocate the protocol in Table 1. Irrespective of how an institution chooses to image ballistic trauma patients, the authors of this article strongly discourage attempting to modify or institute a new protocol “on the fly.” We believe that if there is no dedicated missile trauma protocol available, you should use your institutions standard imaging protocols under direct radiologist supervision with the addition of delayed imaging an additional arterial phase or CT cystography based on the “at the scanner” radiologist review of the initial imaging.…”
Section: Imaging Assessmentmentioning
confidence: 99%
“…Additionally, the absence of a contrast leak does not exclude bowel injury and in our experience, high-density endoluminal contrast can limits one’s ability to discern the short segments of bowel hypoattenuation, which occur in missile trauma. A recent retrospective study 25 has shown that the use of only intravenous contrast has similar sensitivity and specificity to triple contrast technique.…”
Section: Wounding Patterns and Understanding Trajectorymentioning
confidence: 99%